Role of the interferons in CD64 and CD169 expressions in whole blood: Relevance in the balance between viral‐ or bacterial‐oriented immune responses - Pénélope Bourgoin; Géraldine Biéchelé; Inès Ait Belkacem; Pierre‐Emmanuel Morange; Fabrice Malergue (Immunity, Inflammation and Disease, 2020)
Abstract Introduction CD64 expression increases on neutrophils during bacterial infections. Recently an increase in CD169 expression has been discovered on monocytes during viral infections. Generally, interferons α (IFNsα) and IFNsγ are key drivers of the infectious host immune response. The purpose of this study was to explore if a link exists between these IFNs and both biomarkers. Methods Whole blood samples from healthy volunteers were stimulated with either IFNs, interleukins, or infectious extracts, to mimic an infectious state. Expressions of CD64 and CD169 were assessed in these samples by multiple flow cytometry methods, over precise kinetics. Results The expression of CD64 was statistically higher in samples stimulated with IFNγ, and CD169 in those stimulated with IFNα (and all other type I IFNs). Surface expressions are directly induced by their respective IFNs via Janus kinase/signal transducer and activator of transduction pathways within 6 to 8 hours of incubation. Mixing both types of IFNs seemed to indicate that they partially inhibit each other. Conclusions The induction of CD169 on monocytes and CD164 on neutrophils by type I and type II IFNs confirms the relevance of these markers for assessing between a viral‐ vs bacterial‐oriented immune response.